Menstrual Hygiene: Knowledge and Practice among Adoles-cent Girls of Rural Sabarkantha District - Agarwal, Vijay Agarwal; Fancy, Manish J; Shah, Harsh; Agarwal, Akshita S; Shah, Jay Harish; Singh, Snehil (National Journal of Community Medicine, 2017)
Introduction: Menarche is a psychological, social as well as behavioural transition for an adolescent girl from girlhood to womanhood. Menstrual hygiene is most important, still neglected area of concern. The objective of the study was to find out menstrual pattern, knowledge and practice for menstrual hygiene among adolescent girls. Method: A cross sectional study was undertaken in a rural area of Sabarkantha district. Randomly selected 250 adolescent girls were inter-viewed using predesigned pretested questionnaire. Results: It was evident that 35.6% participants were aware about menstruation before their menarche and important sources of information were mothers in 54.2% girls. 14.8% respondents used only sanitary napkin during menstruation. 83.8% changed absorbent 1 to 2 times a day. Conclusion: This study has highlighted the need of adolescent girls to have accurate and adequate information about menstruation before the menarche.